High thermal conductivity of epoxy composites via micro-zone enhanced 3D interconnected nickel skeleton. Issue 17 (1st December 2020) - Bao, Di; Cui, Yexiang; Xu, Fei; Li, Meiling; Li, Kaka; Zhang, Xiguang; Liu, Zhanjian; Zhu, Yanji; Wang, Huaiyuan
Abstract: The composites with high thermal conductivity (TC) have attracted extensive attention in thermal management fields. Incorporating a three dimensional (3D) thermal transport framework in polymer is one of the most effective ways to improve the TC of composites. However, most micro-zone of those 3D thermal transport framework is filled with polymers with very low TC, leading to limited TC improvement of polymer composites. Herein we presented a novel 3D boron nitride (BN)/nickel foam (NF)/epoxy (EP) composite with high TC. Results indicated that as a good reinforced filler with high TC, BN was homogeneously dispersed in epoxy and fully filled into 3D NF micro-zone to get obvious TC increase of the BN/NF/EP composites. With the micro-zone enhancement strategy, the prepared BN/NF/EP-50 composite demonstrated excellent thermal conductive property. The obtained TC (5.14 W m −1 K −1 ) is approximately 24 and 5 times higher than that of epoxy and NF/EP composite, respectively. This research potentially provides a unique way to design and fabricate high TC 3D materials with the micro-zone enhancement strategy.